1981
DOI: 10.1128/aem.42.4.704-707.1981
|View full text |Cite
|
Sign up to set email alerts
|

Modified enrichment-serology procedure for detection of salmonellae in soy products

Abstract: A modified enrichment-serology (MES) procedure was used to reduce the time necessary for salmonella analysis. Naturally contaminated samples of soy products were preenriched in 1% proteose peptone for 6 h at 37°C followed by inoculation into tetrathionate broth for 18 h at 37°C. Two drops of the tetrathionate sample were inoculated into M broth. After incubation at 37°C for 6 h, 0.85 ml of the mixture was formolized, and 0.1 ml of polyvalent H antiserum was added. After incubation in water bath at 50°C for 1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Research efforts to channel selective enrichment cultures away from the sequential plating and biochemical screening steps to more rapid diagnostic tests, including enrichment serology (34), immunofluorescence (35), enzymelinked immunosorbent assay (26) and lysine-iron-cystineneutral red broth (5.15), have met with limited success. Recent work clearly showed that method brevity through incubation of preenrichment cultures for short (4 to 6 h) periods of time is not feasible (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research efforts to channel selective enrichment cultures away from the sequential plating and biochemical screening steps to more rapid diagnostic tests, including enrichment serology (34), immunofluorescence (35), enzymelinked immunosorbent assay (26) and lysine-iron-cystineneutral red broth (5.15), have met with limited success. Recent work clearly showed that method brevity through incubation of preenrichment cultures for short (4 to 6 h) periods of time is not feasible (6).…”
Section: Resultsmentioning
confidence: 99%
“…Novobiocin concentrations of 5 to 80 t-Lg/ml have been used with limited success to increase the selectivity of liquid (18,22,34) and solid (19,23,27) media through inhibition of competitive flora, notably Proteus and Citrobacter spp. In the present study, addition of novobiocin (40 t-Lg1 ml) to SC and TBG failed to markedly increase sensitivity of the standard and 6-h standard methods, but apparently compensated for the low selectivity of SC 35 and TBG 35 in direct enrichment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…impedcnce/conductance (Smith ef al. 1989), fluorescent antibody (Kodrigucs and Kroll 1990), enrichment scrology (Surdy andHaas 1981: 1Iumbcrt cf al. 1990), enzyme immunoassay (Araj and Chugh 1987;Lambiri et al 1990; van Pouckc 1990), latex agglutination (Hadfield rf ul.…”
Section: Introductionmentioning
confidence: 99%